Patient Portal Use Among Older Adults: What Is Really Happening Nationwide?. (April 2020) - Nahm, Eun-Shim; Zhu, Shijun; Bellantoni, Michele; Keldsen, Linda; Charters, Kathleen; Russomanno, Vince; Rietschel, Matt; Son, HyoJin; Smith, Leslie
Patient portals (PPs), secure websites that allow patients to access their electronic health records and other health tools, can benefit older adults managing chronic conditions. However, studies have shown a lack of PP use in older adults. Little is known about the way they use PPs in community settings and specific challenges they encounter. The aim of this study was to examine the current state of PP use in older adults, employing baseline data (quantitative and qualitative) from an ongoing nationwide online trial. The dataset includes 272 older adults (mean age, 70.0 years [50-92]) with chronic conditions. Findings showed that the majority of participants (71.3%) were using one or more PPs, but in limited ways. Their comments revealed practical difficulties with managing PPs, perceived benefits, and suggestions for improvement. Further studies with different older adult groups (e.g., clinic patients) will help develop and disseminate more usable PPs for these individuals.